2011
DOI: 10.2527/jas.2010-3125
|View full text |Cite
|
Sign up to set email alerts
|

Effects of tryptophan supplementation on aggression among group-housed gestating sows1

Abstract: The objective of this study was to determine the effects of dietary Trp supplementation on mixing-induced aggression and the associated stress, and on reproductive performance in gestating sows. After weaning, sows were mixed in pens with electronic sow feeders on concrete-slatted floors. Each pen housed 21 ± 2.8 sows, with approximately 2.7 ± 0.43 m(2)/sow of floor space allowance. Multiparous sows (n = 168) from 8 breeding groups were used, with 4 groups assigned to a control diet and 4 groups assigned to a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
17
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 26 publications
(41 reference statements)
4
17
0
Order By: Relevance
“…Parity 2 sows were more aggressive, fought more frequently, tended to fight for longer periods, and won more fights at mixing compared with parity 1 sows. These results are consistent with previous studies in which older sows were more aggressive at mixing compared with younger sows (Strawford et al 2008;Li et al 2011). Since focal sows were young (in parity 1 and 2) in the group, focal sows won few fights (ranged between 26 and 8% of total fights) in which they were involved, which agrees with results of previous studies that younger sows won few fights compared with older sows (Krauss and Hoy 2011;Li et al 2012).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Parity 2 sows were more aggressive, fought more frequently, tended to fight for longer periods, and won more fights at mixing compared with parity 1 sows. These results are consistent with previous studies in which older sows were more aggressive at mixing compared with younger sows (Strawford et al 2008;Li et al 2011). Since focal sows were young (in parity 1 and 2) in the group, focal sows won few fights (ranged between 26 and 8% of total fights) in which they were involved, which agrees with results of previous studies that younger sows won few fights compared with older sows (Krauss and Hoy 2011;Li et al 2012).…”
Section: Discussionsupporting
confidence: 92%
“…Since focal sows were young (in parity 1 and 2) in the group, focal sows won few fights (ranged between 26 and 8% of total fights) in which they were involved, which agrees with results of previous studies that younger sows won few fights compared with older sows (Krauss and Hoy 2011;Li et al 2012). Focal sows were also less aggressive during nighttime than daytime, as reported previously (Arey and Edwards 1998;Li et al 2011).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…However studies with rainbow trout have shown that dietary supplementation with l-Trp for 7 days before mixing-stress resulted in an inhibition of aggressive behavior and a reduced secretion of stress hormones, whereas 3 days of l-Trp supplementation before mixing-stress have no effects (Winberg et al, 2001;Lepage et al, 2003). Li et al (2011) shown dietary supplementation of l-Trp (0.29%) at 2.3 times of the control amount for 3 days prior social stress did not effectively reduce aggression of gestation sows at mixing. Therefore, the necessity and the amount of time for short term supplementation of l-Trp before mixing on controlling stress of pigs facing stress need to be further investigated.…”
Section: Discussionmentioning
confidence: 97%
“…Such behavior can be modulated by supplementation with low doses of tryptophan (Trp). Diets rich in Trp can modulate behavior in various species, including fish (matrinxã Brycon amazonicus; Wolkers, Serra, Hoshiba, & Urbinati, 2012), sows (Li, Baidoo, Johnston, & Anderson, 2011), dogs (Bosch, Beerda, Hendriks, van der Poel, & Verstegen, 2007), horses (Grimmett, & Sillence, 2005), Wistar rats (Kantak, Hegstrand, Whitman, & Eichelman, 1980), and mice . Tryptophan deficiency might also lead to an intensification of aggression in several species, including humans .…”
Section: Introductionmentioning
confidence: 99%